The Wee1 kinase inhibitor MK1775 suppresses cell growth, attenuates stemness and synergises with bortezomib in multiple myeloma. (21st April 2020) - Liang, Long; He, Yanjuan; Wang, Haiqin; Zhou, Hui; Xiao, Ling; Ye, Mao; Kuang, Yijin; Luo, Saiqun; Zuo, Yuna; Feng, Peifu; Yang, Chaoying; Cao, Wenjie; et al.
Summary: Multiple myeloma stem‐like cells (MMSCs) are responsible for initiation and relapse, though novel treatment paradigms that effectively eradicate MMSCs are yet to be developed. Selective inhibition of the cell cycle regulatory kinase Wee1 by MK1775 is being explored as a potential anti‐cancer therapeutic. We report that higher expression of Wee1 is correlated with poor survival in multiple myeloma (MM). The MM models and patient‐derived CD138 + plasma cells are particularly sensitive to the growth‐inhibitory effects of the Wee1 inhibitor MK1775. MK1775 induces Mus81‐Eme1 endonuclease‐mediated DNA damage in S‐phase cell cycle that results in a blockade of replication and then apoptosis. Furthermore, MK1775 strongly suppresses the features of stemness in vitro, in vivo and in primary CD138 + cells by decreasing ALDH1 + cell fraction and the expression of ALDH1 . In addition, co‐treatment of MK1775 with bortezomib is synergistic in vitro and in vivo . Bortezomib, although it enhances ALDH1 + cells, when combined with MK1775 abrogates this stimulatory effect on stemness. Considering MM as an invariably incurable malignancy due to the presence of heterogenic myeloma stem‐like cells, our study presents inhibition of Wee1 as a promising targeted therapy for MM and provides a compelling rationale to further investigate the activity of MK1775 against myeloma in clinical settings.